(untitled) - Nelson, Dave (New York, 1998)
Managers learn all about the revolutionary techniques behind Honda of America's record success and how to apply them to their own companies. In Powered by Honda managers, for the first time, get the full story behind Honda America's meteoric rise from a struggling Japanese transplant to an American automotive giant. The authors detail the evolution of Honda's supply-based excellence program which, among other things, entails developing great suppliers rather than merely leveraging existing ones
Keywords: Automobile industry and trade,Ngành sản xuất và mua bán xe máy,American Honda Motor Company,Công ty xe hơi Honda Hoa Kỳ; Production control,Quản lý sản xuất,Management,Quản trị; United States,Hoa Kỳ